Tinjauan Yuridis Pembagian Waris Anak Diluar Nikah Berdasarkan Hukum Waris Islam Dan KUHPerdata - Damayanti, Windi Etika; Sahruddin, Sahruddin (Faculty of Law, University of Mataram, 2024)
The purpose of the study is to determine the inheritance rights of illegitimate children based on Islamic Inheritance Law and Indonesia Civil Code Inheritance Law and to find out the similarities and differences in the distribution of inheritance property to illegitimate children in Islamic Inheritance Law and Civil Code Inheritance Law. This research is the normative legal research method. The types of legal materials are primary, secondary, and tertiary legal materials. The results of this research explain the inheritance rights of illegitimate children according to Islamic Inheritance Law and the Inheritance Law of the Indonesia Civil Code; And reveal the similarities and differences in the distribution of inheritance of illegitimate children according to Islamic Inheritance Law and Indonesia Civil Code Inheritance Law.